KEBIJAKAN UPAH MINIMUM KABUPATEN/KOTA : STUDI IMPLEMENTASI PADA PERUSAHAAN DI KABUPATEN KARAWANG - Siska Widianti Motip; Hanny Purnamasari Purnamasari; Ani Nurdiani Azijah (JIA: Jurnal Ilmiah Administrasi, 2020)
This research is motivated by a phenomenon in society that increases the amount of minimum wages especially in Karawang Regency, every year it creates problems including reduction workers/laborers and companies that have closed or moved out of the region because they are unable to pay the amount of wages minimum in Karawang Regency. From the background descrition, the purpose of this study is to know The success of implementing policies on district / city minimum wages in companies in Karawang Regency according to the theory of implementation of Van Meter and Van Horn (in Winarno, 2013: 158). Method this research uses descriptive method with a qualitative approach. Data obtained through literature and in-depth interviews with informants related to the focus of this research. Processing and analysis techniques the data is carried out through three activities that occur simultaneously, namely data reduction, data presentation and conclusion or verification. Based on the research results that the implementation of the minimum wage policy the companies in Karawang Regency are running well and smoothly, but there are several shortcomings that needs attention. Such as legal imperfections or legal defects that occur during deliberation determination of the 2020 UMK Karawang because there is no agreement between the entrepreneur and the worker/laborer.